The Effect of Germination on Chemical Constituents of Broad Beans and Chickpeas Seeds (Baghdad Science Journal, 2007)
This study was carried out to find out the effect of germination of broad beans and chickpeas seeds for different periods on their antinutritional factors content ( Trypsin inhibitor and Phytic acid ) and the chemical constituents of germination seeds compared with the control samples (ungerminated seeds) . The results indicated asignificant increase (P